Performance of Oats and Legumes Sown in Pure Stands and Mixtures - BAYOUMI , M. A.; RAHMAN, A. H. M. MOJIBUR (The Libyan Journal of Agriculture, 2023)
In a field trial of 1975-76 and 1976-77. oats and two legume species. Vetch and Egyptian clover were grown in pure stands and mixtures. Egyptian clover in pure stand gave the highest forage yield. The percentage of dry matter increased with increasing oats in the mixture. Forage yield was increased with increasing legume component in the mixture. The percentage of crude protein, ether extract and mineral matter was higher in Egyptian clover than those of oats, vetch in pure stand, and in the different combinations of mixture.